2021
DOI: 10.52336/acm.2021.10.6.02
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants as a defence against reactive oxygen species

Abstract: Reactive oxygen species are formed as a natural product of metabolic processes occurring in the organism or under the influence of external factors. Under homeostasis, they play an important role as a cellular signaling device. During oxidative stress, when they are produced in excess, they can cause damages to proteins, lipids, carbohydrates or nucleic acids. Exposure of cells and extracellular structures to free radicals activate natural mechanisms to eliminate free radicals and their derivatives. The aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Cows are particularly vulnerable to disturbance of homeostasis and one of the reasons is an intensification of milk yield in recent years [ 8 ]. Oxidative stress plays a crucial role in the occurrence of many diseases, reproductive disorders, and reduced milk yield [ 9 , 10 ]. Organisms have antioxidant systems that consist of antioxidant enzymes such as catalase, glutathione peroxidase, and superoxide dismutase, as well as non-enzymatic antioxidants: retinol, tocopherol, ascorbic acid, glutathione, α,α-diphenyl-β-picrylhydrazyl (DPPH), and others [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cows are particularly vulnerable to disturbance of homeostasis and one of the reasons is an intensification of milk yield in recent years [ 8 ]. Oxidative stress plays a crucial role in the occurrence of many diseases, reproductive disorders, and reduced milk yield [ 9 , 10 ]. Organisms have antioxidant systems that consist of antioxidant enzymes such as catalase, glutathione peroxidase, and superoxide dismutase, as well as non-enzymatic antioxidants: retinol, tocopherol, ascorbic acid, glutathione, α,α-diphenyl-β-picrylhydrazyl (DPPH), and others [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, according to a study by Tan et al, gallic acid inhibited the expression of the main adipogenesis genes SREBP-1c and PPAR-γ by 37.2% and 51.1%, respectively, thus confirming its inhibition of adipogenesis effect through the inhibition of preadipocyte differentiation [26]. Catalase and peroxidase decompose the active oxygen generated in the body into water and oxygen molecules, thereby regulating homeostasis [27]. However, when an excessive production of active oxygen, lipid and protein denaturation, adipocyte metabolism disorders, and lowering of the body's metabolic function are present, a homeostasis imbalance occurs, which ultimately leads to obesity.…”
Section: Quantification Of Major Substance Using Hplcmentioning
confidence: 84%
“…SOD2 is predominantly found in mitochondria. SOD3 is found in blood serum, tissues, and body fluids (including synovial fluid and cerebrospinal fluid) [139]. A study showed that SOD activity was elevated in rats with acetic acid-induced UC compared to the control group.…”
Section: Superoxide Dismutasementioning
confidence: 99%